2003
DOI: 10.1074/jbc.m301042200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiogenesis and Angiogenesis-dependent Tumor Growth by the Cryptic Kringle Fragments of Human Apolipoprotein(a)

Abstract: Apolipoprotein(a) (apo(a)) contains tandemly repeated kringle domains that are closely related to plasminogen kringle 4, followed by a single kringle 5-like domain and an inactive protease-like domain. Recently, the anti-angiogenic activities of apo(a) have been demonstrated both in vitro and in vivo. However, its effects on tumor angiogenesis and the underlying mechanisms involved have not been fully elucidated. To evaluate the anti-angiogenic and anti-tumor activities of the apo(a) kringle domains and to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 48 publications
4
61
0
Order By: Relevance
“…Wound Migration Assay-The effect of rhLK68 on HUVEC migration stimulated by angiogenic factors including bFGF, VEGF, and HGF was assayed in a monolayer denudation assay as previously described (10). Confluent HUVECs were wounded by scraping, washed twice with phosphate-buffered saline to remove cellular debris, and incubated in endothelial cell basal medium-2 supplemented with 1% fetal bovine serum for 24 h, following which rhLK68 proteins (1 or 3 M) were added.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wound Migration Assay-The effect of rhLK68 on HUVEC migration stimulated by angiogenic factors including bFGF, VEGF, and HGF was assayed in a monolayer denudation assay as previously described (10). Confluent HUVECs were wounded by scraping, washed twice with phosphate-buffered saline to remove cellular debris, and incubated in endothelial cell basal medium-2 supplemented with 1% fetal bovine serum for 24 h, following which rhLK68 proteins (1 or 3 M) were added.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Recombinant Human LK68 -Recombinant human LK68 (rhLK68), which comprises cryptic kringle fragments of apo(a) containing KIV-9, KIV-10, and KV, was expressed and purified from Escherichia coli as described previously (10). Briefly, rhLK68 expressed as an inclusion body was collected, refolded in vitro, and purified using lysine-Sepharose column chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional assays for Lp (a) oxidation are needed 101 , as are more studies to address the implication of Lp (a) Some questions remain in relation to the controversial anti-tumor function of Lp(a) 110 . In experimental studies a reduction of tumor cells growth by apo(a) was demonstrated 111,112 . The degradation of apo(a) inside of Lp(a), produces various size of kringles and this process was associated with anti-angiogenesis and anti-tumor properties 110 .…”
Section: Current Perspectives 13mentioning
confidence: 99%
“…8 Earlier studies showed an anti-angiogenic activity of apo(a), suggesting a possible role for apo(a) in bridging atherogenesis and angiogenesis in vivo. 8,9 Recently, Kim et al 10 have demonstrated that apo(a) kringle LK68, consisting of KIV-9-KIV-10-KV, inhibits the proliferation and migration of endothelial cells in vitro and suppresses angiogenesis-dependent growth of human colon (HCT-15) and lung (A549) tumors in vivo when administered systemically. LK68-expressing murine colorectal cancer cells (CT26) restricted hepatic metastases to smaller sizes, prevented peritoneal dissemination, and significantly suppressed colon tumor growth in different experimental models.…”
mentioning
confidence: 99%